Radiation‐induced mesothelioma among long‐term solid cancer survivors: a longitudinal analysis of SEER database. (10th February 2016) - Farioli, Andrea; Ottone, Marta; Morganti, Alessio G.; Compagnone, Gaetano; Romani, Fabrizio; Cammelli, Silvia; Mattioli, Stefano; Violante, Francesco S.
Abstract: We investigated the association between external beam radiotherapy (EBRT) and pleural and peritoneal mesothelioma among long‐term (>5 years) solid cancer survivors. We analyzed data from the US Surveillance, Epidemiology, and End Results (SEER) program (1973–2012). We fitted survival models adjusted by age, gender, race, year, surgery, and relative risk of primary mesothelioma in the county of residence (proxy for individual asbestos exposure). We estimated hazard ratios [HR] with reference to nonirradiated patients. We distinguished between scattered and direct irradiation to study the dose–response. We observed 301 mesotheliomas (265 pleural; 32 peritoneal; 4 others) among 935, 637 patients. EBRT increased the risk of mesothelioma (any site; HR 1.34, 95% CI 1.04–1.77). We observed an increased risk of pleural mesothelioma (HR for EBRT 1.34, 95% CI 1.01–1.77), but we did not find signs of a dose–response relationship (HR for scattered irradiation 1.38; HR for direct irradiation 1.23). On the opposite, only direct peritoneal irradiation was associated with peritoneal mesothelioma (HR 2.20, 95% CI 0.99–4.88), particularly for latencies ≥10 years (HR 3.28, 95% CI 1.14–9.43). A competing risks analysis revealed that the clinical impact of radiation‐induced mesothelioma was limited by the high frequency of competing events. The cumulative incidence function of mesothelioma after 40 years of observation was very low (nonirradiated patients 0.00032, irradiated patients 0.00055).EBRT might be a determinant of mesothelioma. Longer latency periods are associated with higher risks, while the dose–response seems nonlinear. The clinical impact of mesothelioma after EBRT for primary solid cancers is limited. Abstract : Patients treated with external beam radiotherapy for solid cancers present an increased incidence of mesothelioma compared to nonirradiated patients. However, the clinical impact of radiation‐induced mesothelioma is extremely limited.